[tex]\texttt{Folosim formula: } \\
(a \pm b) = a^2 \pm 2ab + b^2 \\ \\
\texttt{Rezolvare: } \\ \\
a=(2\sqrt 3 - 1)^2+(\sqrt 3+2)^2 = \\
=[(2\sqrt 3)^2 - 2\times 2\sqrt 3 \times 1+1^2]+[(\sqrt 3)^2 +2 \times \sqrt 3 \times 2 + 2^2]= \\
= [12 - 4\sqrt 3 +1]+[3 +4\sqrt 3 + 4]= \\
= \underline{12} - \underline{\underline{4\sqrt 3}} +\underline{1}+\underline{3} +\underline{\underline{4\sqrt 3}} + \underline{4}
=20 - \underline{\underline{4\sqrt 3}} +\underline{\underline{4\sqrt 3}} = \boxed{20}[/tex]